THE EFFECT OF BIOURINE ON GROWTH AND YIELD THE ONION PLANT ON ALLUVIAL SOIL - Wandi, Tiodorus; ., Rahmidiyani; Budi, Setia (Jurnal Sains Pertanian Equator, 2020)
An onion plant is the commodity that must be expanded, intensively in West Borneo, one of the suitable soils be used for planting this plant is alluvial soil. This research is aim to know the best dose of Bio urine on growth and the onion plant yield on alluvial soil. The sample of this research is Completely Randomise Design (RCD). b1 treatment control, b2 treatment: Bio urine 50 ml + 950 ml water = 1 L, b3 treatment: Bio urine 100 ml + 900 ml water = 1 L, b4 treatment: Bio urine 150 ml + 850 ml water = 1 L, b5 treatment: Bio urine 200 ml + 800 ml water = 1 L, b6 treatment: Bio urine 250 ml + 750 ml water = 1 L. So that can be achieved 6 treatments, 4 repetitions and 3 observation samples. There are some of observation variable on this research are the plant stature(cm), leaves(sheet), sprouts, tubers per clump(tubers), root, volumes(ml)and dried weigh tubers(g). The result of this research show that the bio urine treatment evidently influenced on plant stature 2 weeks after planted, abstract influent on all observation variables.Keywords :Onion, Bio urine, Alluvial Soil